The relationship between sexual function and irrational beliefs and self-concept in married women in Tehran - Lavasani, Maryam; Taheri, Afsaneh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to investigate the relationship between sexual function and irrational beliefs and self-concept in women. Method: The present study is a correlational descriptive method. The statistical population of this study includes married women aged 20-40 years living in Tehran (regions 1 and 3) who were studied in the spring of 1400. In this study, the sample size was estimated by Tabachink and Fidel formulas of 116 people, which was reduced to about 140 people, and in order to be optimized for generalization to the community, we were able to use 216 people who were selected by sampling method and selected voluntarily. The Rosen et al.’s (2000) Women’s Sexual Performance Questionnaire, Jones (1969) Irrational Beliefs Questionnaire, and Beck and Steer (1978) Self-Esteem Questionnaire were used to collect data. The present study was analyzed using regression test. SPSS software version 25 was also used for data analysis. Results: The results showed that among the components of sexual function, psychological stimulation, humidity and satisfaction in a negative way and sexual pain in a positive and significant way predicts irrational beliefs in women (P<0.01). The results also showed that among the components of sexual function, sexual desire (p<0.05, β= 0.191) and satisfaction (p<0.05, β= 0.117) were positive and sexual pain (p<0.05, β= 0.404) negatively and significantly predicts self-concept in women. Conclusion: Based on the findings of the present study, psychological stimulation predicts negative moisture and satisfaction and sexual pain positively and significantly predicts irrational beliefs in women. It also predicts sexual desire and satisfaction in a positive way and sexual pain in a negative and meaningful way in women.